Hepatotoxicity associated with the dietary supplement OxyELITE Pro™ — Hawaii, 2013. Issue 3 (2nd November 2015) - Johnston, David I.; Chang, Arthur; Viray, Melissa; Chatham‐Stephens, Kevin; He, Hua; Taylor, Ethel; Wong, Linda L.; Schier, Joshua; Martin, Colleen; Fabricant, Daniel; Salter, Monique; Lewis, Lauren; et al.
Abstract : Dietary supplements are increasingly marketed to and consumed by the American public for a variety of purported health benefits. On 9 September 2013, the Hawaii Department of Health (HDOH) was notified of a cluster of acute hepatitis and fulminant hepatic failure among individuals with exposure to the dietary supplement OxyELITE Pro™ (OEP). HDOH conducted an outbreak investigation in collaboration with federal partners. Physicians were asked to report cases, defined as individuals with acute onset hepatitis of unknown etiology on or after 1 April 2013, a history of weight‐loss/muscle‐building dietary supplement use during the 60 days before illness onset, and residence in Hawaii during the period of exposure. Reported cases' medical records were reviewed, questionnaires were administered, and a product investigation, including chemical analyses and traceback, was conducted. Of 76 reports, 44 (58%) met case definition; of these, 36 (82%) reported OEP exposure during the two months before illness. No other common supplements or exposures were observed. Within the OEP‐exposed subset, two patients required liver transplantation, and a third patient died. Excessive product dosing was not reported. No unique lot numbers were identified; there were multiple mainland distribution points, and lot numbers common to cases in Hawaii were also identified in continental states. Product analysis found consumed products were consistent with labeled ingredients; the mechanism of hepatotoxicity was not identified. We report one of the largest statewide outbreaks of dietary supplement‐associated hepatotoxicity. The implicated product was OEP. The increasing popularity of dietary supplements raises the potential for additional clusters of dietary supplement‐related adverse events. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Hawaii Department of Health (HDOH) conducted a statewide outbreak investigation in collaboration with federal partners of a cluster of acute hepatitis and fulminant hepatic failure among individuals with exposure to the dietary supplement OxyELITE Pro™.